Axially oriented guest induced crystallization in syndiotactic polystyrene unstretched fibers. (16th July 2021) - Cozzolino, Antonietta; Rizzo, Paola; Gallo, Chiara; Bianchi, Riccardo; Daniel, Christophe; Guerra, Gaetano
Abstract: Guest-induced crystallization of amorphous s-PS fibers, although prepared with slow take-up speeds (e.g., 80 m/min) and in the absence of mechanical stretching, unexpectedly leads to high degrees of axial orientation (0.7 <  f c  < 0.8) of co-crystalline phases. Similar high degrees of axial orientation can be maintained after suitable guest removal procedures, leading to nanoporous-crystalline (NC) phases. High degrees of orientation are even maintained after high temperature (e.g., 200 °C) treatments leading to dense crystalline α phases, although this phase transition implies change of polymer conformation from helical to zig-zag planar. Hence, guest induced crystallization of amorphous s-PS fibers not only leads to NC forms (suitable for removal of organic pollutants from the environment) or to co-crystalline forms with active guests (e.g., suitable for antimicrobial release) but also lead, without stretching, to axial orientation. For the disordered NC form, fiber patterns are for the first time reported, showing only four diffraction peaks, which suggest the occurrence of a hexagonal packing of chain axes of s (2/1)2 polymer helices. The NC nature of this disordered crystalline form is clearly confirmed by tests of perchloroethylene uptake, from dilute aqueous solutions (500 ppb). Graphical abstract: Image 1 Highlights: Guest-induced crystallization induces high degrees of axial orientation in unstretched amorphous s-PS fibers. High degrees of axial orientation in s-PS fibers are maintained after guest removal, leading to nanoporous-crystalline phases. High degrees of axial orientation in s-PS are even maintained after treatments at 200 °C leading to dense crystalline α phase. A fiber pattern of the disordered NC form of s-PS shows a hexagonal packing of chain axes of s(2/1)2 polymer helices. The NC nature of disordered crystalline form is confirmed by tests of perchloroethylene uptake, from dilute aqueous solutions. Abstract : Guest-induced crystallization of amorphous unstretched syndiotactic polystyrene (s-PS) fibers leads to high degrees of axial orientation (0.7 <  f c  < 0.8) of co-crystalline phases. This orientation can be maintained after suitable guest removal procedures, leading to nanoporous-crystalline (NC) phases, as well as after high temperature (e.g., 200 °C) treatments, leading to dense crystalline α phases although this phase transition implies change of polymer conformation from helical to zig-zag planar form.